Students’ and Employers’ Perceptions of Employability Skills in Uganda - Tagulwa, Elvaida Agnes; Owino, Philip; Muwonge, Francis; Kaahwa, Maria Goretti (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
The study evaluated employability skills as they were perceived by students of Kyambogo University and employers. The population comprised of students and employers. Students were from the faculty of science and the sample size consisted of 226 students from six departments. The employers were from organisations where these students do their industrial training. The sample size of the employers consisted of 19 participants from thirteen organisations. The specific objective of the study was to evaluate students’ and employers’ perceptions of employability skills. Employability skills were evaluated basing on their categorisation: professional skills, personal skills, and interpersonal skills (Byrne, 2022; Yorke & Night, 2007; Chowdhury & Miah, 2019). Quantitative results revealed that there was a statistically significant difference in the perceptions of important employability skills between students of Kyambogo University and employers (P=0.00 < 0.05). Statistical and qualitative analysis gave important employability skills as theoretical knowledge and skills, creativity, innovation and entrepreneurship, positive attitude, and collaboration and team work. Strategies to enable students acquire employability skills include: job market analysis, collaboration and partnerships with local industries to do research; provide enough practicals and field studies. It was therefore recommended that Kyambogo University should develop collaboration and partnerships with local industries to do research.